Model Simulasi Risiko Rantai Pasok Material Proyek Konstruksi Gedung - Hatmoko, Jati Utomo Dwi; Kistiani, Frida (MEDIA KOMUNIKASI TEKNIK SIPIL, 2017)
Delays related to materials are one of main problems of construction project. An effective supply chain management has a significant role in preventing this type of delay. The aim of this research is develop risk simulation model of construction supply chain in buildings. The materials include steel bars, steel profiles, formwork, and precast concrete, as they are considered the main building material. The supply chain risks are classified from supply, control, process, and demand sides. Monte Carlo simulation has been performed using Cristal Ball software. Risk identification was done through literature review, site observation, and interviews with 29 contractor personnel  working for nine building projects. The simulation results show that the minimum, maximum, and most frequent delays (in days), as follows: steel bars (2.20. 17.05, 11.24); steel profiles (2.12, 15.10, 9.75), formwork (1.79, 16.04, 10.45), precast concrete (1.76, 15.61, 10.24).  The sensitivity analysis shows that delay due to change order from client is the most sensitive for  steel bars, steel profiles, and formwork of 25.5%, 37.4%, dan 17%, respectively. The results of this research is useful for contractors and owners who can use them as a guidance in identifying, predicting, and mitigating supply chain risks for a successful project.